2014
DOI: 10.1249/mss.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Protein Turnover Signaling in Slow-Twitch Muscle during Exercise

Abstract: These results fit with a regulation of protein breakdown triggered by FoxO3a and Ulk1 pathways after AMPK activation and Akt/MTOR inhibition. Furthermore, our data suggest that mitochondrial fission is quickly increased, and mitochondrial fusion is unchanged during exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 36 publications
8
84
0
3
Order By: Relevance
“…Findings from our study indicate that expression of both LC3I and LC3II increases in response to the exercise program, with a significant elevation of the LC3II/I ratio, supporting a possible enhanced number of autophagosomes. However, whether this raise is the consequence of an increased autophagosome formation or a defect in their degradation through the lysosome remains to be elucidated (Pagano et al 2014). To further understand the changes in the markers of autophagy, LC3II measurements should be combined with other markers of autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from our study indicate that expression of both LC3I and LC3II increases in response to the exercise program, with a significant elevation of the LC3II/I ratio, supporting a possible enhanced number of autophagosomes. However, whether this raise is the consequence of an increased autophagosome formation or a defect in their degradation through the lysosome remains to be elucidated (Pagano et al 2014). To further understand the changes in the markers of autophagy, LC3II measurements should be combined with other markers of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of ULK-1 phosphorylation by feeding has been associated with an activation by AMP-activated protein kinase α in humans (Schwalm et al 2015), and short-term aerobic exercise seems to increase the expression of ULK-1 phosphorylated at Ser 555 (Moller et al 2015). In mice, LC3I is lipidated in response to running exercise, and this is accompanied by decreased ULK-1 Ser 757 phosphorylation (Pagano et al 2014). The decreased expression in the autophagy-inhibitory Ser 757 phosphorylated ULK-1 described in the current study supports the notion of an exercise-induced autophagic stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endurance exercise training can induce autophagy, and, appropriately, intracellular energetic stress elicited by exercise seems to be the nexus for autophagy induction, as ultra-endurance exercise (Jamart et al, 2012a,b), running to exhaustion (Pagano et al, 2014;Vainshtein et al, 2015b) and exercise commenced when fasted (Jamart et al, 2013;Møller et al, 2015) all upregulate autophagic signalling processes. However, in well-trained human skeletal muscle there is no synergistic effect of prior fasting on autophagy signalling compared with commencing the exercise bout in the fed state, with exercise intensity mitigating the largest autophagic response to contraction (Schwalm et al, 2015).…”
Section: Reduced Energy Availabilitymentioning
confidence: 99%
“…These findings occurred with concomitant increases in the expression of UPS components, in particular atrogin-1, MuRF-1, and PSMA1, although the activity of the 26S proteasome itself was interestingly repressed after exercise (71). Laboratory animal studies have also demonstrated a more pronounced upregulation in autophagy-lysosomal gene expression and associated FOXOrelated activity when endurance exercise is performed in the fasted state compared with the fed state (69), particularly in slow-twitch muscle fibers (70), although these findings have not been confirmed in human muscle. Results from our laboratory confirm the effects of endurance exercise on UPSmediated proteolysis, as atrogin-1 and MuRF-1 expression were upregulated during recovery from moderate endurance exercise in recreationally active individuals (72).…”
Section: Exercise and Nutritional Modulation Of Skeletal Muscle Protementioning
confidence: 99%